2003
DOI: 10.1124/mol.63.3.532
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Functional Expression of Organic Anion Transporting Polypeptide 3 at Rat Choroid Plexus Epithelial Cells and Its Involvement in the Cerebrospinal Fluid-to-Blood Transport of Estrone-3-Sulfate

Abstract: The cerebrospinal fluid-to-blood efflux transport of estrone-3-sulfate (E 1 S) via the blood-cerebrospinal fluid barrier (BCSFB) may play an important role in regulating E 1 S levels in the brain. Here, we investigated the efflux transport of E 1 S at the BCSFB using conditionally immortalized rat choroid plexus epithelial cells (TR-CSFB) and identified the responsible transporter. The [ 3 H]E 1 S uptake by TR-CSFB cells was composed of saturable and nonsaturable components, and the K m and V max values of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
(52 reference statements)
2
42
0
Order By: Relevance
“…1). These results suggest that mouse oatp2 and 3 play roles at the BCSFB similar to those in the case of rat BCSFB (Gao et al 1999;Ohtsuki et al 2003).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…1). These results suggest that mouse oatp2 and 3 play roles at the BCSFB similar to those in the case of rat BCSFB (Gao et al 1999;Ohtsuki et al 2003).…”
Section: Discussionsupporting
confidence: 63%
“…Our recent report has shown that rat oatp3, but not oatp1, is localized at the brush-border membrane of rat choroid plexus epithelial cells (Ohtsuki et al 2003). In mouse, oatp3 mRNA was detected in choroid plexus, but oatp1 mRNA was not (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations